Do shopping lists help in saving time during online grocery shopping? A qualitative study among italian consumers - Sodano, Marta (2020)
Numerous past studies have analised the usage of shopping lists for grocery shopping. Among all their functions, they seem to save time in store. With the incumbency of the digital channel, literature has started to investigate the role of shopping lists for egrocery shopping. One particular study suggested that shopping lists may not apport benefits in terms of saving time, since the online channel reduces the time lag already, as past research has mainly underlined. However, product research task may still need improvements. Therefore, the present study will investigate whether shopping lists enable to save time during egrocery shopping.